2014
DOI: 10.3906/bot-1301-53
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of transgenic tobacco plants expressing the dehydration-responsive RD22 gene of Vitis vinifera to salt stress

Abstract: Salinity is one of the most common environmental stresses affecting grapevine productivity. In order to analyze the contribution of the dehydration-responsive RD22 gene of Vitis vinifera L. (VvRD22) to salt tolerance improvement, Agrobacteriummediated transformation in the tobacco model plant (Nicotiana benthamiana) was carried out and transgenic lines were subjected to in vitro and ex vitro salt treatments for physiological response evaluation. Under in vitro salt stress, the transgenic lines exhibited higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The DEG encoding glutathione S-transferase (GST) U17 (GSTU17) - like was continuously downregulated and found in Profile 0, which acts as a negative regulator of salt and drought stress response [41]. In addition, The DEGs encoding dehydration-responsive protein RD22 and Ca 2+ -dependent protein kinase 29 (CDPK29) were assigned to Profile 6 (Figure 6 and Table S10), which is involved in plant adaptation to drought and salinity stress [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…The DEG encoding glutathione S-transferase (GST) U17 (GSTU17) - like was continuously downregulated and found in Profile 0, which acts as a negative regulator of salt and drought stress response [41]. In addition, The DEGs encoding dehydration-responsive protein RD22 and Ca 2+ -dependent protein kinase 29 (CDPK29) were assigned to Profile 6 (Figure 6 and Table S10), which is involved in plant adaptation to drought and salinity stress [42,43].…”
Section: Resultsmentioning
confidence: 99%
“…In a related study, similar increased chlorophyll retention was observed in transgenic plants expressing the stressresponsive gene VvRD22 with respect to the WT upon exposure to 400 mM NaCl (Jardak-Jamoussi et al, 2014).…”
Section: Response Of T1 Progenies To Salt Stressmentioning
confidence: 59%
“…Based on the hypothesis that a difference in gene regulation is an indicator of an adaptive response, many differentially-expressed genes under abiotic stress conditions were used to transform model or agronomically-interesting plants (Zhang and Blumwald, 2001 ;Figueras et al, 2004 ;Mukhopadhyay et al, 2004) in order to improve abiotic stress tolerance and productivity. In this context, a salt-induced VvRD22 gene from grapevine was recently characterized to be involved in salt stress tolerance in tobacco plants (Jardak-Jamoussi et al, 2014).…”
Section: Differential Expression Of Genes Under Salinitymentioning
confidence: 99%